Imitatio, intertextuality and culture. About "De cartón piedra" by Joan Manuel Serrat and "A la sombra de un león" by Joaquín Sabina. A study of Comparative Literature - Rodríguez Santos, José María (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
This work deals with the cultural and intertextual relationships between two songs, one by Joan Manuel Serrat and the other by Joaquín Sabina. It is based on the assumptions about literary creation that advocate that originality can only occur within a tradition and the comparative analysis of the texts focuses on the similarities and differences of the common elements and symbols contained in both songs and the relationship of these with tradition and culture, demonstrating that these are decisive in both the creation and reception processes.